GEOLOGICAL CHARACTERIZATION OF POTENTIAL DAM SITES (International Journal of Food and Nutritional Sciences, 2022)
The paper covers various aspects of geological site exploration, including the exploration techniques, methodology,stages, data collection, analysis, and presentation. The review also includes a case study of a dam site failure toillustrate the importance of thorough exploration and accurate data analysis. The study emphasizes the significanceof proper geological exploration practices to prevent potential failures. Properly characterizing the site's geologicalconditions ensures the safety, stability, and success of the dam, serving as the basis for informed engineeringdecisions